2017
DOI: 10.1097/md.0000000000006532
|View full text |Cite
|
Sign up to set email alerts
|

Short, double elastic nailing of severely displaced distal pediatric radial fractures

Abstract: Rationale:Short double elastic nailing is a minimal invasive, modified ESIN (elastic stable intramedullary nailing) technique for severely displaced distal radial fracture in children. The aim of this technical report is to introduce our new method and evaluate the final results of the procedure.Patient concerns:We reviewed retrospectively 24 patients who underwent short double elastic nailing due to distal radial fractures between November 2012 and December 2015. Indications for surgery included closed, sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…There are only a few reports on these fractures [4][5][6][7]. Reduction and surgical immobilisation for paediatric DRDMJ fractures remain a challenge [6,7]. Many surgical immobilisation techniques have been reported, but each type of fixation has limitations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are only a few reports on these fractures [4][5][6][7]. Reduction and surgical immobilisation for paediatric DRDMJ fractures remain a challenge [6,7]. Many surgical immobilisation techniques have been reported, but each type of fixation has limitations.…”
Section: Discussionmentioning
confidence: 99%
“…However, paediatric fractures in the area of the distal radius diaphyseal metaphyseal junction (DRDMJ) represent a unique problem, namely, they are usually located too distally to be treated by classic ESIN fixation and too proximal for conventional K-wires fixation [3,4]. The treatment of paediatric DRDMJ fractures is a challenge, as evidenced by the numerous surgical techniques described, including conventional methods (crossed K-wires, open reduction and plate fixation and conventional ESIN fixation) and modified techniques (transepiphyseal intramedullary Kirschner wire fixation, pre-bending intramedullary nailing fixation, and short, double elastic nailing fixation) [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Although various types of intramedullary nailling devices, such as Targon DR and Micro nail have been used for fixation of unstable fractures of the radius and reported to be associated with satisfactory results. 8 , 9 , 22 , 23 experience and studies on Sonoma Wrx are limited. 24 , 25 In our previous prospective randomized pilot study, we compared standard volar locking plate with intramedullary fixation using the Sonoma Wrx, and found that clinical and radiological outcome of two techniques were comparable and satisfactory in treatment of distal radius fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Intramedullary nailing has been introduced as a less invasive technique for internal fixation of both intra- and extra-articular distal radius fractures and for correction of post-traumatic deformity. 7 - 9 With the advantages of minimum soft-tissue dissection, intramedullary nailing promotes effective fracture stabilization and healing. 10 Clinical studies showed that in comparison to volar plating, intramedullary nailing provides better or comparable early postoperative functional outcomes and reduce the incidence of carpal tunnel syndrome, a major complication of distal radius fracture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation